Working in uncertainty: Organizational behavior of contingent college teachers in the Philippines - Eva Joy Canto Palma; George R. West (Institute of Advanced Engineering and Science, 2023)
Several researchers have previously written about factors that contribute to the organizational commitment of employees. However, there are only few empirical studies on the impact of organizational commitment on organizational citizenship behavior (OCB), especially among non-permanent employees and how these behaviors have been impacted by perceived organizational support (POS). This study investigated the contextual relationships of organizational commitment and OCB, along with the mediation effect of POS on those relationships in the context of contingent teachers in Philippine state universities and colleges. A survey was conducted in selected state universities and colleges in the Philippines with contingent teachers for academic year 2019-2020 as respondents. Findings of the study showed that the targeted population generally rate their OCB higher than their organizational commitment or any of the subcategories thereof. They also rated OCB higher than the perceived support that they receive from their given organizations. Results also found that POS, although correlating with OCB, did not mediate any of associated relationships. The results indicate that contingent faculty members develop and maintain commitment to their organizations from sources other than the perceived support that they receive from their organizations.